Unveiling the psychological traits of multi-marathoners: Insights from TIPI personality trait analysis - Leo Lundy; Richard B. Reilly; Neil Fleming; Dominika Wilczyńska (PLoS ONE, 2025)
Objectives Multi-marathoners, athletes dedicated to completing 100 + marathons, represent a unique endurance sport subculture. This study examines their psychological traits using the Ten Item Personality Inventory (TIPI) and Latent Class Analysis (LCA) to identify personality-based profiles and subgroup differences. Methods An online cross-sectional survey of 593 multi-marathoners (56% men, 44% women, mean age =  53.87, SD =  9.91, countries = 22) collected TIPI data. Reliability was assessed using Cronbach’s Alpha and Guttman’s Lambda 6. Statistical analyses included Mann-Whitney U tests, ANOVA Aligned Rank Transform (ART), Wilcoxon post-hoc tests, and Spearman’s correlations to examine personality differences across gender, age and health variables. LCA identified distinct personality subgroups. Normative TIPI data served as a comparison benchmark. Results Multi-marathoners exhibited higher conscientiousness (F(1,591) =  2.42, p < 0.001) but lower emotional stability (F(1,591) =  5.525, p < 0.001) than the general population, suggesting strong goal-directed behaviour but challenges in stress management. Women showed higher agreeableness (W =  50809, p < 0.00091), while age-related differences were not statistically significant. LCA revealed four personality-based subgroups, including those with high resilience and others with health vulnerabilities. Conclusion Multi-marathoners display distinct psychological traits, particularly high conscientiousness and lower emotional stability. These findings highlight the need for tailored psychological interventions to support multi-marathon athletes' participation and well-being. Future research should explore longitudinal patterns and explore the efficacy of psychological interventions to enhance participation and well-being.